2013
DOI: 10.3892/ijmm.2013.1547
|View full text |Cite
|
Sign up to set email alerts
|

P7 peptides targeting bFGF sensitize colorectal cancer cells to CPT-11

Abstract: Abstract. The low survival rate of patients with colorectal cancer (CRC) is mainly due to the drug resistance of tumor cells to chemotherapeutic agents. It has been reported that basic fibroblast growth factor (bFGF) is an essential factor involved in the epigenetic mechanisms of drug resistance, which provides a novel potential target for improving the sensitivity of tumor cells to chemotherapeutic agents. In this study, we first demonstrate that a novel bFGF antagonist, peptide P7, previously isolated by pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Anti-bFGF antibodies were shown to enhance radiosensitivity in oesophageal SCC through a reduction in colony formation in-vitro [ 36 ]. In addition, targeting of bFGF by a peptide has been shown to improve chemo-sensitivity in CRC [ 43 ]. These findings in the literature and within our study show that LIF and bFGF together both play important roles in cancer progression and treatment response in many cancers and may influence both OAC cells and host immunity by functioning as part of the active cytokine network.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-bFGF antibodies were shown to enhance radiosensitivity in oesophageal SCC through a reduction in colony formation in-vitro [ 36 ]. In addition, targeting of bFGF by a peptide has been shown to improve chemo-sensitivity in CRC [ 43 ]. These findings in the literature and within our study show that LIF and bFGF together both play important roles in cancer progression and treatment response in many cancers and may influence both OAC cells and host immunity by functioning as part of the active cytokine network.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as disclosed by Samie and colleagues, ascorbic acid treatment substantially reduced the expression of bFGF, bFGFR, PDGF, PDGFR, and PLC- γ in the HT29 cell line [ 101 ]. The low survival rate of CRC patients is principally due to the chemotherapeutic resistance of tumor cells; relatedly, it has been reported that bFGF could regulate the epigenetic mechanisms of drug resistance, thus representing a novel potential target for improving the sensitivity of tumor cells to chemotherapeutic agents [ 102 ]. According to preclinical findings, clinical studies confirmed bFGF as a clinicopathological factor and highlighted its possible role as a marker of metastatic progression and patient prognosis [ 103 , 104 ].…”
Section: Bfgf and Cancermentioning
confidence: 99%